The Agility and Endurance SPV BBC Ungaran Volleyball Players (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aims to analyze the levels of agility and aerobic endurance (VO₂max) of male volleyball athletes at SPV BBC Ungaran as a basis for evaluating their physical condition and designing a training program. This study employed a quantitative, descriptive approach using a survey method. The study subjects consisted of 14 active athletes participating in a regular training program. Data collection was conducted using the T-test agility test to measure agility and the beep test to measure aerobic endurance (VO₂max). Data were analyzed using descriptive statistics, including mean, standard deviation, and percentage distribution. The results indicated that the athletes’ agility levels were predominantly in the moderate category (72%), while their aerobic endurance (VO₂max) also fell into the moderate category (79%). These findings suggest that the athletes’ biomotor capacity is not yet optimal to meet the demands of fast-paced, high-intensity volleyball. These findings suggest that improving athletes’ performance requires a more structured, sport science-based training program, particularly through the application of periodization and specific agility and aerobic endurance training. This study has limitations due to the relatively small sample size and the use of a descriptive design without intervention, so the results cannot yet be widely generalized. Therefore, future research is recommended to use an experimental design with a larger sample size to obtain more comprehensive and applicable results. Additional materials: This study is supported by 30 references, 3 tables (data categories and frequency distributions), and 2 figures/diagrams of measurement results illustrating the athletes’ agility and endurance profiles.